Structural analysis of the Chopin Etudes as prerequisite to physical practice - Van Wyk, Wessel (College of Music, 2025)
This study treats visualisation of the printed score prior to practice as first step towards comprehension and learning of a composition. It obviates senseless mechanical solutions to technical difficulties. The purpose of this study is to outline a systematic procedure of analysis which will enable the performer to understand the musical structure of a Chopin etude in its broader and finer detail. The analytical procedure also supports thorough investigation into Chopin's interpretative indications. The study is geared towards the pianist with a mature technique who will realise that visual analysis can also benefit technical execution. Three etudes of contrasting nature and content - Op.25, No.2 and Op.10, Nos.12 and 4 - are analysed. The analyses concentrate on the characteristic elements of form, melody, and harmony. The synthesis of these structural elements with interpretative detail attempts to provide the performer with an ideal interpretation of each work. iv Astounding, canorous, enchanting, alembicated, and dramatic, the Chopin studies are exemplary essays in emotion and manner. In them is mirrored all of Chopin, the planetary as well as the secular Chopin. When most of his piano music has gone the way of all things fashioned by mortal hands, these studies will endure, will stand for the nineteenth century, as Beethoven crystallised the eighteenth and Bach the seventeenth centuries in piano music. Chopin is a classic.